To close the eyes or not : the effects of occipital alpha power induced by eye closure on auditory entrainment - Duman, Deniz (2018)
Neuronal oscillations facilitate extracting sensory information from the environment through optimization of rhythmic fluctuation in excitation and inhibition cycles of neurons; which is defined as neural entrainment. Although research suggests entrainment to frequency modulated (FM) speech-like rhythmic sounds, factors influencing entrainment are still open for discovery. With this purpose, the current work tackled the understudied daily strategy, eye closure, in auditory perception domain. Neural and behavioral effects of eye closure on auditory entrainment were investigated. Eleven participants detected near-threshold gaps (sound breaks) embedded in 2.8 Hz FM stimuli both eyes open and closed conditions. Electroencephalogram (EEG) data were also obtained from eight of the participants. Eye closure was hypothesized to induce occipital alpha oscillations, associated with decreased neural and behavioral effects of entrainment and results in enhanced gap detection performance compared with eyes open condition. Results revealed that, as hypothesized, eye closure increased occipital alpha power. Moreover, increased 2.8 Hz neural activity and participants’ modulated behavioral gap detection performance suggested neural and behavioral auditory entrainment to 2.8 Hz FM sound stimuli both in eyes open and closed conditions. Contrary to the main hypothesis, closing the eyes did not influence the overall gap detection performance. However, first evidence of auditory entrainment under eye closure condition was provided. Although the current data have limitations, all in all, an interaction of two distinct auditory perception mechanisms -neural entrainment and cortical alpha band oscillations- are suggested to involve in perception of speech-like sound stimuli. Further, this interaction was proposed to influence auditory perception differently under eye open and closed periods, raising a firm background for further research on possible benefits of eye closure on sensory information processing.